Retificação plana tangencial dos ferros fundidos nodular, vermicular e cinzento em várias condições de corte - Lima, Mariana Landim Silveira (2016)
In a scenario of increasing competitiveness of the global industrial sector and with a consumer market increasingly demanding, there is an increased demand for new materials and, consequently, possibilities to explore new research and technological advances towards the development of new manufacturing methods or the improvement of existing technologies. In the case of cast irons, new grades of them have been developed so that their mechanical properties have been improved, making them more competitive with steel, expanding the applications and thus represents great economic gain for metallurgy and manufacturing sectors. This increases the interest and creates new opportunities to study these materials and identify how they respond in terms of the surface integrity, tool wear, cutting forces, among others, when machined by grinding operation. In this context, due to the lack of results from grinding of cast irons and studies comparing grindability among several grades of cast irons found in the literature, this work aims to generate scientific and technological contribution to the metallurgical and metal working sector through roughness results (Ra and Rz parameters) and evaluation and analysis of the subsurface integrity of three cast iron grades (gray, compacted graphite and nodular). The machining trials were performed on a surface grinding machine with silicon carbide grinding wheel at different cutting conditions. The input variables were the radial depth of cut (15 and 30 μm), worktable speed, vw (5 and 10 m/min) and the abrasive grain size of the grinding wheel. The results showed that surface roughness increased with the radial depth of cut for all materials tested; and the lowest values were obtained for gray cast iron. Also, roughness was sensitive to variation of worktable speed and the lowest values were obtained after machining with vw = 5 m/min. With respect to the abrasive grain size, as it decreased the roughness values increased to gray and nodular cast iron grades. Furthermore, grinding burns marks were observed on the surfaces of nodular cast iron and compacted graphite iron grades after grinding the smallest grain size, contrary to what is usually reported in literature. However, no evidence of severe thermal damages below the machined surfaces of all cast iron grades was observed after analyzing the results of hardness and the SEM micrograph images.